Strategies For Addressing The Spillover Effect Of Mosaic Warfare In The South China Sea Conflict To Achieve National Security Stability - Alwi, Muhamad Bashori; Suhanda, Chairi; Setiawan, Dany; Ricky, Muchamad; Hadawang, Rusdyanto (Security Intelligence Terrorism Journal (SITJ), 2024)
The South China Sea is a strategic area rich in natural resources and a crucial international shipping and trade route, making it a focal point of territorial disputes between China, the Philippines, Vietnam, Malaysia, Brunei, and Taiwan. This conflict escalates tensions and the potential spillover effects of mosaic warfare that can impact Indonesia's national security and stability. This journal analyzes the strategic implications of the South China Sea conflict for Indonesia, exploring defensive and proactive strategies to mitigate risks and enhance national resilience. This research uses a qualitative descriptive approach based on historical analysis and content analysis, successfully identifying key areas of concern such as increased maritime security risks, the need for enhanced military capabilities, and the importance of regional and international cooperation. Proposed strategies include increased diplomatic engagement, strengthening defense capabilities, intelligence and security technology cooperation, and diversifying economic and trade routes. Indonesia must adopt a multifaceted and proactive strategy to protect its interests amidst regional instability, strengthen diplomatic relations within ASEAN and globally, enhance military and surveillance capabilities, and ensure economic resilience against potential disruptions in maritime trade routes. Public education and adherence to international law are also crucial for maintaining regional peace and security.